The experience of the parenteral form of ibandrinic acid administration in different clinical situations of treatment of postmenopausal osteoporosis - L. A. Marchenkova; E. V. Makarova (Лечащий Врач)
The article presents two clinical cases illustrating the experience of using ibandronate in patients with different clinical types of postmenopausal osteoporosis, including those undergoing medical rehabilitation procedures. Ibandronic acid is highly effective in reducing of vertebral fracture risk and in increasing spinal bone mineral density and also has a good tolerance, safety profile and a convenient administration regimen. Given the evidence base of clinical trials, ibandronate may be a treatment option for postmenopausal women with uncomplicated osteoporosis and with osteoporotic fractures. In particular, the appointment of the drug is justified in patients undergoing rehabilitation after an osteoporotic fracture and associated surgical treatment. Physical therapy in combination with the prescription of pharmaceuticals affecting the bone remodeling allows achieving better results in the rehabilitation of patients with osteoporotic fractures.